I need your help. Can you answer this one?

Find the value of **B** for any real numbers **A** and **B** such that

**A + B** = **\(A^{2}\) - \(B^{2}\)** = **AB** ≠ **0** .a

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest\[\alpha+\beta = \alpha^{2}-\beta^{2}\ = (\alpha+\beta)(\alpha-\beta)\] Here, if \(\alpha+\beta = 0\), the equation will be true, therefore one of the answer is \(\beta = -\alpha\), but if \(\alpha+\beta \neq 0\), you will get \(1 = \alpha-\beta\) or \(\beta = \alpha-1\). \(\beta\) may be represented as \(\beta = -\alpha, \alpha-1\)

Log in to reply